2018
DOI: 10.1103/physrevb.97.214405
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent relaxation of dipole-exchange magnons in yttrium iron garnet films

Abstract: Low energy consumption enabled by charge-free information transport, which is free from ohmic heating, and the ability to process phase-encoded data by nanometer-sized interference devices at GHz and THz frequencies are just a few benefits of spin-wave-based technologies. Moreover, when approaching cryogenic temperatures, quantum phenomena in spin-wave systems pave the path towards quantum information processing. In view of these applications, the lifetime of magnonsspin-wave quanta-is of high relevance for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 66 publications
2
33
0
Order By: Relevance
“…However, in the case of YIG films grown on GGG, the story is more complex. GGG is a geometrically frustrated magnetic system [22] and it has long been known that at temperatures below 70 K, it exhibits paramagnetic behaviour that has been reported to increase damping in films grown on its surface [23][24][25]. The behaviour of GGG at mK temperatures is yet to be thoroughly characterised [26][27][28], but recent results at mK temperatures have suggested that magnon damping in YIG films grown on GGG is higher than expected if the properties of the YIG system alone are considered arXiv:1903.02527v3 [cond-mat.mes-hall] 25 Oct 2019 Dashed lines are linear fits, the details of these fits are summarised in table I.…”
mentioning
confidence: 99%
“…However, in the case of YIG films grown on GGG, the story is more complex. GGG is a geometrically frustrated magnetic system [22] and it has long been known that at temperatures below 70 K, it exhibits paramagnetic behaviour that has been reported to increase damping in films grown on its surface [23][24][25]. The behaviour of GGG at mK temperatures is yet to be thoroughly characterised [26][27][28], but recent results at mK temperatures have suggested that magnon damping in YIG films grown on GGG is higher than expected if the properties of the YIG system alone are considered arXiv:1903.02527v3 [cond-mat.mes-hall] 25 Oct 2019 Dashed lines are linear fits, the details of these fits are summarised in table I.…”
mentioning
confidence: 99%
“…The similar temperature behavior of the magnon BEC and parametrically injected magnons brings hope that an extremely long BEC lifetime can be achieved in ultra pure bulk YIG samples, where, as it has been found in Refs. [21,39], the relaxation rate of parametric magnons monotonically decreases from room to cryogenic temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the dimensionless data from Ref. [21] were scaled to coincide with the BEC relaxation rate at one temperature point T = 340 K. As is clearly seen from Fig. 4, the relaxation rates of both groups of magnons have the same qualitative and quantitative temperature dependence.…”
Section: At Relatively High Temperatures Tmentioning
confidence: 97%
See 2 more Smart Citations